Six days in October : the stock market crash of 1929 - Blumenthal, Karen (Atheneum Books for Young Readers, 2002)
A comprehensive review of the events, personalities, and mistakes behind the Stock Market Crash of 1929, featuring photographs, newspaper articles, and cartoons of the day.